THE EFFECT OF USING DIGITAL MARKETING ON INCREASING BUSINESS PERFORMANCE MSMES IN JAMBI CITY - Ifwan Adinata; Meilita Tryana Sembiring; Sugiharto Pujangkoro (CV. RADJA PUBLIKA, 2024)
This article aims to investigate the impact of digital marketing utilization on the performance enhancement of Micro, Small, and Medium Enterprises (MSMEs) in Jambi City. The study focuses on the government's programs aimed at improving the quality of MSMEs in Jambi City through training, mentoring, and coaching. To approach this issue, marketing management theory serves as a framework to enhance business performance in MSMEs in Jambi City. Data collection was conducted by distributing questionnaires to 106 respondents, namely business owners in Jambi City who have been using digital marketing for at least 1 year, and analyzed quantitatively using multiple regression analysis. The research findings reveal a simultaneous influence between digital marketing and business performance with a strong correlation level. Moreover, the hypothesis partially indicates that the benefit dimension has the highest influence, while the incentive program has the lowest influence. Collectively, the five dimensions of digital marketing contribute to influencing the business performance of MSMEs in Jambi City by 56.5%, with the remaining being influenced by other factors. This study offers a novel measurement concerning the utilization of digital marketing in MSMEs based on relevant literature review.